X - 4y = 4
3x + y = 10
Soluções para a tarefa
Respondido por
2
{x - 4y = 4 → Multiplicando esta parte de cima por (-3)
{3x + y = 10
{- 3x + 12y = - 12 → Somando tudo:
{3x + y = 10
- 3x + 12y + 3x + y = 10 - 12
13y = - 2
y =![- \frac{2}{13} - \frac{2}{13}](https://tex.z-dn.net/?f=-+%5Cfrac%7B2%7D%7B13%7D+)
Aplicando o "y" em uma das equações acima:
3x + y = 10
3x -
= 10
3x = 10 +![\frac{2}{13} \frac{2}{13}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B13%7D+)
3x =![\frac{130}{13} + \frac{2}{13} \frac{130}{13} + \frac{2}{13}](https://tex.z-dn.net/?f=+%5Cfrac%7B130%7D%7B13%7D+%2B+%5Cfrac%7B2%7D%7B13%7D+)
3x =![\frac{132}{13} \frac{132}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B132%7D%7B13%7D+)
x =![\frac{132}{13}.\frac{1}{3} \frac{132}{13}.\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B132%7D%7B13%7D.%5Cfrac%7B1%7D%7B3%7D+)
x =![\frac{132}{39} \frac{132}{39}](https://tex.z-dn.net/?f=%5Cfrac%7B132%7D%7B39%7D+)
{3x + y = 10
{- 3x + 12y = - 12 → Somando tudo:
{3x + y = 10
- 3x + 12y + 3x + y = 10 - 12
13y = - 2
y =
Aplicando o "y" em uma das equações acima:
3x + y = 10
3x -
3x = 10 +
3x =
3x =
x =
x =
Perguntas interessantes
Sociologia,
11 meses atrás
Administração,
11 meses atrás
Português,
11 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás